Pedagogi, Andragogi dan Heutagogi sebagai Kontinum di Perguruan Tinggi: Deskripsi dan Model Pengukuran - Amiruddin Amiruddin; Nurlaela Nurlaela; Muhammad Hasim S.; Wirawan Setialaksana (Lembaga Penelitian Mahasiswa Penalaran UNM, 2022)
This study aims to apply the pedagogical, andragogical and heutagogy approaches together in the lecture/learning process. This approach has novelty because there is no empirical evidence regarding the use of the three together in the classroom. This research was conducted in order to investigate the implementation of the three in the classroom using a descriptive quantitative approach by first checking the measurement model of the three. The sample in this study was 316 students voluntarily filling out electronic questionnaires. The collected data will be analyzed using a measurement model to investigate the validity and reliability of the model. Its constructs and indicators. The results of the research using the measurement model show that the three constructs are valid and reliable constructs. The indicators that make up the construct are also valid and reliable indicators. Descriptive statistics show that the lecture process in the midst of a pandemic is dominated by the andragogical approach. The heutagogical approach as the ideal approach used in higher education shows the lowest average response. Further research can be conducted by analyzing the relationship between the approaches as a continuum.